2011
DOI: 10.1002/mus.21965
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced muscle growth is muscle‐specific and age‐dependent

Abstract: Exercise-induced activation of SCs and regulation of gene expression are muscle-specific and age-dependent. Perturbed sensitivity to exercise in older mice provides insight into sarcopenia and potential treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 57 publications
1
35
1
Order By: Relevance
“…Half the mice had access to a voluntary running wheel for voluntary exercise (Ex) for the first 3 wk of the treatment period, as reported (5). A previous study showed quadriceps from 18-mo mice were refractory to hypertrophy following 3 wk of voluntary exercise, whereas younger 8-mo mice were responsive (44); this experiment tested whether NO-donor treatment could change the responsiveness to exercise and induce muscle growth in the 18-mo group. Groups were control (C, oil only, n ϭ 6), Ex (n ϭ 8), I (n ϭ 4), and I ϩ Ex (n ϭ 3).…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Half the mice had access to a voluntary running wheel for voluntary exercise (Ex) for the first 3 wk of the treatment period, as reported (5). A previous study showed quadriceps from 18-mo mice were refractory to hypertrophy following 3 wk of voluntary exercise, whereas younger 8-mo mice were responsive (44); this experiment tested whether NO-donor treatment could change the responsiveness to exercise and induce muscle growth in the 18-mo group. Groups were control (C, oil only, n ϭ 6), Ex (n ϭ 8), I (n ϭ 4), and I ϩ Ex (n ϭ 3).…”
Section: Methodsmentioning
confidence: 95%
“…Muscle wasting results from atrophy of individual fibers, loss and expansion of motor units (24, 37, 79) that becomes increasingly severe from late-middle age to senescence in both fast-and slow-twitch muscles (63) and ultimately weakness limits function and quality of life. Current treatments, such as exercise and growth-promoting drugs, are not completely effective, in part as we do not fully understand the many facets of age-related atrophy.Progressive refractoriness of satellite cells (SC) to stimuli that promote growth in young mice, such as stretch (43) and exercise (36,44,45), is a major contributor to age-related atrophy. Muscle SC are required to maintain mass and repair muscle and are involved in growth via proliferation (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously observed a blunted hypertrophic response in older females following long-term RT (Bamman et al, 2003;Ivey et al, 2000;Kosek et al, 2006). Although the underlying mechanism has not been well-defined, the divergent extent of hypertrophy in old females may occur in part from reduced myogenic aptitude (Gallegly et al, 2004;Leiter et al, 2011), which could conceivably impair the regenerative processes activated in response to mechanical loading.…”
Section: Introductionmentioning
confidence: 91%
“…Muscle mass is strictly regulated by various factors and can adapt to physical exertion by increasing the amount and size of contractile proteins (Leiter et al 2011). One of the most powerful negative regulators of muscle growth is myostatin (McPherron and Lee 1997).…”
mentioning
confidence: 99%